Cytotoxic effects of neem oil in the midgut of the predator Ceraeochrysa claveri - Scudeler, Elton Luiz [UNESP]; Garcia, Ana Silvia Gimenes [UNESP]; Padovani, Carlos Roberto [UNESP]; Pinheiro, Patricia Fernanda Felipe [UNESP]; Santos, Daniela Carvalho dos [UNESP] (Elsevier B. V., 2015)
Studies of morphological and ultrastructural alterations in target organs have been useful for evaluating the sublethal effects of biopesticides regarded as safe for non-target organisms in ecotoxicological analyses. One of the most widely used biopesticides is neem oil, and its safety and compatibility with natural enemies have been further clarified through bioassays performed to analyze the effects of indirect exposure by the intake of poisoned prey. Thus, this study examined the cellular response of midgut epithelial cells of the adult lacewing, Ceraeochrysa claveri, to neem oil exposure via intake of neem oil-contaminated prey during the larval stage. C. claveri larvae were fed Diatraea saccharalis eggs treated with neem oil at concentrations of 0.5%, 1% and 2% throughout the larval stage. The adult females obtained from these treatments were used at two ages (newly emerged and at the start of oviposition) in morphological and ultrastructural analyses. Neem oil was found to cause pronounced cytotoxic effects in the adult midgut, such as cell dilation, emission of cytoplasmic protrusions, cell lysis, loss of integrity of the cell cortex, dilation of cisternae of the rough endoplasmic reticulum, swollen mitochondria, vesiculated appearance of the Golgi complex and dilated invaginations of the basal labyrinth. Epithelial cells responded to those injuries with various cytoprotective and detoxification mechanisms, including increases in cell proliferation, the number of calcium-containing cytoplasmic granules, and HSP 70 expression, autophagic processes and the development of smooth endoplasmic reticulum, but these mechanisms were insufficient for recovery from all of the cellular damage to the midgut. This study demonstrates that neem oil exposure impairs the midgut by causing sublethal effects that may affect the physiological functions of this organ, indicating the importance of studies of different life stages of this species and similar species to evaluate the safe and compatible integrated use of biopesticides.
Keywords: Biopesticide; Chrysopidae; Green lacewing; Toxicity; Ultrastructure